2004
DOI: 10.1007/s00134-004-2203-y
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled study of the efficacy of hypromellose and Lacri-Lube combination versus polyethylene/Cling wrap to prevent corneal epithelial breakdown in the semiconscious intensive care patient

Abstract: Polyethylene covers are as effective as HL in reducing the incidence of corneal damage in intensive care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0
15

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 20 publications
4
90
0
15
Order By: Relevance
“…Eight of thirty "lubricating eye drop" patients demonstrated corneal staining with fluorescein, which signified EK, contrasted with only 1 of 30 moisture chamber patients [43]. Koroloff et al [44] studied 110 ICU patients with reduced or absent blink reflex. Groups either received hypromellose drops and Lacrilube every 2 h or had polyethylene covers on the eyes to create a "moisture chamber."…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight of thirty "lubricating eye drop" patients demonstrated corneal staining with fluorescein, which signified EK, contrasted with only 1 of 30 moisture chamber patients [43]. Koroloff et al [44] studied 110 ICU patients with reduced or absent blink reflex. Groups either received hypromellose drops and Lacrilube every 2 h or had polyethylene covers on the eyes to create a "moisture chamber."…”
Section: Treatmentmentioning
confidence: 99%
“…Eyes in both patient groups were cleaned every 2 h with saline. The study showed that none of the patients developed corneal ulceration in the polyethylene group while four patients experienced ulceration in the hypromellose group [44]. In another report, 146 patients were assigned to receive treatment with either a "moisture chamber" created with swimming goggles and gauze soaked in sterile water (closed chamber), or ocular lubricants with securing tape over the eyes (open chamber).…”
Section: Treatmentmentioning
confidence: 99%
“…It was found also that the reduced eyelid reflex at least five times per minute is an important risk factor associated with the prolonged use of sedatives and muscle relaxants that can lead to lagophthalmos with consequent prolonged eye opening that predisposes to dryness and corneal abrasion. [11][12] Other studies confirm these findings. 13,17 It was observed, so, that the muscular relaxation promoted by the action of neuromuscular blocking causes the decrease of the tonus of the eyelid which favors the incomplete closure.…”
Section: Turquiamentioning
confidence: 66%
“…Salienta-se que, em outros estudos (15,16) , o efeito do filme de polietileno também foi superior para a prevenção do olho seco, quando comparado ao uso do colírio lubrificante gotas associado à lágrima artificial em gel (p=0,12) (15) e à pomada ocular (p=0,519)…”
Section: Introductionunclassified